The question of reaching the pinnacle (apogee) of human life and development - Nazarova Nigora Ravshanovna. (Euro Asian Journal Publishing, 2023)
This article briefly discusses what characteristics a person must embody to reach the peak of his life and development, and what he should pay attention to in his professional development. At the same time, it was also emphasized that the role of teachers in educating each person to achieve a level of professional excellence is incomparable.
Keywords: Subject; pedagogical acmeology; personality; comprehensive personality